Taos and its artists - Luhan, Mabel Dodge (Duell, Sloan, & Pearce New York, 1947)
Contains an essay about the artists in Taos, New Mexico: brief biographies, portraits, and samples of their work. [Luhan often invited artists and writers to Taos.].
Chiefly illustrations.
36802
Keywords: Artist -- Taos, NM; Painting -- Taos, NM; New Mexico